2019
DOI: 10.1039/c9ra00675c
|View full text |Cite
|
Sign up to set email alerts
|

The conversion of α-pinene to cis-pinane using a nickel catalyst supported on a discarded fluid catalytic cracking catalyst with an ionic liquid layer

Abstract: The Ni/DF3C coated with ionic liquid layer exhibits excellent selectivity toward cis-pinane and stability in the hydrogenation of α-pinene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The hydrogenation of turpentine and its main components, α-pinene and β-pinene, has been researched for many years and continues to the present with different application objectives. However, the number of studies about hydrogenation of monoterpenes directed to the production of renewable fuels is scarce, and they were focused on the production of renewable diesel, and in just one case on jet fuel …”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenation of turpentine and its main components, α-pinene and β-pinene, has been researched for many years and continues to the present with different application objectives. However, the number of studies about hydrogenation of monoterpenes directed to the production of renewable fuels is scarce, and they were focused on the production of renewable diesel, and in just one case on jet fuel …”
Section: Introductionmentioning
confidence: 99%
“…The ionic liquid in the SCILL system also appeared to be useful in the development of an active and selective hydrogenation catalyst, one of the components of which was the discarded fluid cracking catalyst DF3C. The latter was used as a support in the catalytic system containing 10 wt% nickel and ionic liquid (1-ethanol-3-methylimidazolium tetrafluoroborate) [96]. The system was employed for the hydrogenation of α-pinene to cis-pinane and enabled the maintaining of the conversion of α-pinene on the level of about 99% during 13 catalytic cycles, after which the performance of the catalyst deteriorated due to leaching of the ionic liquid.…”
Section: Solid Catalyst With Ionic Liquid Layer (Scill)mentioning
confidence: 99%
“…For instance, Wang et al 9 used a Ni‐supported spent fluid cracking catalyst (Ni/SFCC) for the hydrogenation of α‐pinene and obtained a selectivity of 90.2%. It was observed that the performance of Ni/SFCC could be improved by modifying the catalyst using an ionic liquid 10 . Zhang et al 11 prepared a graphene‐based nickel alloy (Ni‐B/rGO) for the hydrogenation of pinene.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the performance of Ni/SFCC could be improved by modifying the catalyst using an ionic liquid. 10 Zhang et al 11 prepared a graphene-based nickel alloy (Ni-B/rGO) for the hydrogenation of pinene. Their study reported that the selectivity of cis-pinane was more than 96.5%, and the catalyst can be reused eight times.…”
Section: Introductionmentioning
confidence: 99%